Chromatographic profile and bioactive compounds found in the composition of pupunha oil (Bactris gasipaes Kunth): implications for human health - Vasconcelos dos SANTOS, Orquídea; Dias SOARES, Stephanie; Sodré DIAS, Pamela Cristina; de Paula de Almeida DUARTE, Samanta; Lima dos SANTOS, Mayara Priscila; das Chagas Alves do NASCIMENTO, Francisco (Revista de Nutrição, 2022)
Objective The presence of dietary bioactive compounds in the human diet becomes a major factor in combating the etiology of different pathologies. Thus, the aim of this investigation was to evaluate the fatty acids profile, cardiovascular functionality indices, bioactive compounds and spectroscopic pattern of peach palm oil (pupunha oil) and their impact on human health. Methods The oil was obtained by soxhlet extraction; the oil yield and qualities were determined according to the standards of the Association of Official Analytical Chemists. For the fatty acids profile, the practical recommendations of the American Oil Chemists’ Society and of the International Organization for Standardization were followed. Total carotenoids and polyphenols were determined by spectrophotometry; the composition of the chemical groups was determined by infrared spectroscopy. The anti-atherogenic, antithrombogenic and hypocholesterolemic indices were obtained using mathematical models. Results The results showed good quality oil based on acid and peroxyde indices (2.45±0.33mg KOH g-1 and 5.47±1.05mEqkg-1). The main fruit bioactive compound was β-carotene (832.4±0.64µg/100g). The chromatographic profile showed a high saturated fatty acid content (53.74%); unsaturated (46.25%); fats were monounsaturated (39.66%) and polyunsaturated (6.59%). The antiatherogenic, antithrombogenic and hypocholesterolemic indices were, on average, 1.10, 2.04 and 0.84, respectively. The spectroscopic profile exhibited bands with variation from 2918.8cm-1 to 714cm-1. Conclusion The results indicate that the consumption of isolated lipid content of the pupunha palm oil provides health protection with emphasis on the prevention of cardiovascular diseases.